Large-area WSe2 electric double layer transistors on a plastic substrate. (27th April 2015) - Funahashi, Kazuma; Pu, Jiang; Li, Ming-Yang; Li, Lain-Jong; Iwasa, Yoshihiro; Takenobu, Taishi
Abstract: Due to the requirements for large-area, uniform films, currently transition metal dichalcogenides (TMDC) cannot be used in flexible transistor industrial applications. In this study, we first transferred chemically grown large-area WSe2 monolayer films from the as-grown sapphire substrates to the flexible plastic substrates. We also fabricated electric double layer transistors using the WSe2 films on the plastic substrates. These transistors exhibited ambipolar operation and an ON/OFF current ratio of ∼10 4, demonstrating chemically grown WSe2 transistors on plastic substrates for the first time. This achievement can be an important first step for the next-generation TMDC based flexible devices.